2020
DOI: 10.21203/rs.3.rs-37908/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pictures of X-Rays Displayed in Monitors for Deep Learning-Based COVID-19 Screening: Implications for Mobile Application Development

Abstract: As the world faces the COVID-19 pandemic, Artificial Intelligence, in particular, Deep Learning (DL) have been called up for help. Several recent research papers have shown the usefulness of these techniques for COVID-19 screening in Chest X-Rays (CXRs). To make this technology accessible and easy to use for the healthcare workers a natural path is to embed it into a mobile app. In these cases, however, the DL models must be prepared to receive as inputs pictures taken with the smartphones.Trying to raise awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are also some other noticeable challenges in this regard. Experiments performed in [149] have shown that the quality of images in this way is not adequate for managing the smartphone based applications. It is also challenging to get accurate and relevant speech data for developing deep learning models in terms of social distancing norms.…”
Section: Detecting and Diagnosing Covid-19 Patients With No Or Mild C...mentioning
confidence: 99%
“…There are also some other noticeable challenges in this regard. Experiments performed in [149] have shown that the quality of images in this way is not adequate for managing the smartphone based applications. It is also challenging to get accurate and relevant speech data for developing deep learning models in terms of social distancing norms.…”
Section: Detecting and Diagnosing Covid-19 Patients With No Or Mild C...mentioning
confidence: 99%
“…They found that the sensitivity for COVID-19/pneumonia diagnosis was improved based on the mlCXR image interpretation. While one study applied the convolutional neural network model for COVID-19 diagnosis based on the CXR images collected from the Kaggle dataset [19], another study demonstrated that deep learning models failed to classify the CXR images taken from smartphones [20]. Therefore, it is essential to check the sources of images before inputting the images into deep learning models.…”
Section: Related Workmentioning
confidence: 99%